Ефективність окремих агротехнічних заходів при вирощуванні туї західної в умовах Центру України - Шахбатян, Армен Арамович; Shakhbatian, Armen (ЦНТУ, 2024)
В даній випускній кваліфікаційній роботі досліджено ефективність застосування укорінювачів та торфосумішей у технології вирощування туї західної Смарагд в умовах Центру України. Мета досліджень - вивчити ефективність укорінювачів на різних торфосумішах при вирощуванні туї західної Смарагд в умовах Центру України. Встановлено, що найбільш ефективним в умовах Центру України при вирощуванні туї західної Смарагд є укорінення живців за допомогою препарату Ризопон на торфi кислому з рН 2,8 - 3,8. This final qualification work investigates the effectiveness of rooting agents and peat mixtures in the technology of growing western thuja Smaragd in the conditions of the Center of Ukraine. The purpose of the research is to study the effectiveness of rooting agents on different peat mixtures when growing western thuja Smaragd in the conditions of the Center of Ukraine. It was established that the most effective in the conditions of the Center of Ukraine when growing western thuja Smaragd is rooting cuttings using the drug Rizopon on acidic peat with a pH of 2.8 - 3.8.
Efficiency of certain agrotechnical measures in the cultivation of western thuja in the conditions of the Centre of Ukraine
Keywords: туя західна Смарагд; торф; укорінювач; живцi; western thuja Smaragd; peat; rooting agent; cuttings